2021
DOI: 10.3389/fcimb.2020.615343
|View full text |Cite
|
Sign up to set email alerts
|

A Hetero-Multimeric Chitinase-Containing Plasmodium falciparum and Plasmodium gallinaceum Ookinete-Secreted Protein Complex Involved in Mosquito Midgut Invasion

Abstract: Malaria parasites are transmitted by Anopheles mosquitoes. During its life cycle in the mosquito vector the Plasmodium ookinete escapes the proteolytic milieu of the post-blood meal midgut by traversing the midgut wall. This process requires penetration of the chitin-containing peritrophic matrix lining the midgut epithelium, which depends in part on ookinete-secreted chitinases. Plasmodium falciparum ookinetes have one chitinase (PfCHT1), whereas ookinetes of the avian-infecting parasite, P. gallinaceum, have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 74 publications
2
16
0
Order By: Relevance
“…This pivotal degradation process is normally carried out by a chitinase secreted by the parasite. Interestingly, chitinase inhibitors and anti-chitinase antibodies are known to reduce parasite transmission from the vertebrate host to the mosquito, thus suggesting that the peritrophic matrix chitin is a critical feature related to Plasmodium penetration of the midgut [45][46][47]. Considering the major roles of chitinases in the crucial processes of the Plasmodium invasion, it is reasonable to presume that genetic variants of mosquito chitinases can be responsible for the integrity and variable thicknesses of the PM.…”
Section: Discussionmentioning
confidence: 99%
“…This pivotal degradation process is normally carried out by a chitinase secreted by the parasite. Interestingly, chitinase inhibitors and anti-chitinase antibodies are known to reduce parasite transmission from the vertebrate host to the mosquito, thus suggesting that the peritrophic matrix chitin is a critical feature related to Plasmodium penetration of the midgut [45][46][47]. Considering the major roles of chitinases in the crucial processes of the Plasmodium invasion, it is reasonable to presume that genetic variants of mosquito chitinases can be responsible for the integrity and variable thicknesses of the PM.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal bovine serum (FBS) was used as positive control, as it is known to have demonstrated chitinase activity. 11 The purified rPfCHT1-220, À230, and -Triple mutant did not show any measurable chitinase enzymatic activity. However, the elution peaks in the affinity purification chromatograms were observed for -Triple, and À230 mutant proteins (Figure S2).…”
Section: Pfcht1-203 Cysteine Is Highly Reactive and Leads To The Form...mentioning
confidence: 91%
“…In escaping the mosquito midgut, the role played by the Plasmodium ookinete‐secreted chitinases varies among Plasmodium species 10 . However, both long and short chitinase forms bind to chitin have been well demonstrated irrespective of the structural differences of the Plasmodium chitinase protein 11 . Structurally, Plasmodium species with long chitinases have four conserved cysteine residues in the chitin‐binding domain at the C‐terminal compared to the three conserved cysteine residues located in the catalytic domain of the short chitinases 10 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent report showed that PgCHT2 and its ortholog PfCHT1 form high-molecular weight (HMW) complexes, the implications of which are unknown. 58 Sequence alignment of four representative long forms (PvCHT1, PbCHT1, PreCHT1, and PgCHT1) or four short forms (PgCHT2, PfCHT1, PrCHT1, and PreCHT2), lead to the construction of a consensus-like signature sequence for the long and short forms. When the consensus sequence belonging to the long and short forms were aligned, some of the positions were not invariant (Figure 3).…”
Section: Properties Of Plasmodium Chitinasesmentioning
confidence: 99%
“…This regulation is dialed out in short forms along probably compensated with high specific activity. A recent report showed that PgCHT2 and its ortholog PfCHT1 form high‐molecular weight (HMW) complexes, the implications of which are unknown 58 …”
Section: Properties Of Plasmodium Chitinasesmentioning
confidence: 99%